Maturing process of solitary wave train in a step-down chain - 夏继宏 王平建 刘长松 (Chinese physics B, 2012)
In a step-down chain a solitary wave （SW） evolves into an SW train （SWT）, but the formation of well-defined SWT takes time and space and little is known of the process from immature into mature SWT. We therefore perform a detailed numerical study of this process by analysing the local velocity amplitude and peak overlap of immature ordered SWs. The first SW continuously increases to maximal velocity amplitude and peak overlap until it is matured, but for following SWs there exist a minimal and maximal value of local velocity amplitude and, a minimal and maximal value of local peak overlap, clarifying the details of the energy propagation along the stepped chain. The immature and mature SWTs show the same dependence of the phase velocity on the SWs sequence. These provide guidelines for when or where the attention should be paid in the study of SWT.